2005
DOI: 10.1186/1475-9276-4-6
|View full text |Cite
|
Sign up to set email alerts
|

User fees in private non-for-profit hospitals in Uganda: a survey and intervention for equity

Abstract: Background: In developing countries, user fees may represent an important source of revenues for private-non-for-profit hospitals, but they may also affect access, use and equity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…18 There is no significant link between expenditure and official payment probability in the private sector, where most people make official payments (83%), although the point estimate is 0.01 (panel B, columns 4-6). This is consistent with the observation of Amone et al (2005) that patients exempted at Catholic hospitals are typically not poor.…”
Section: Probability Of Bribingsupporting
confidence: 90%
See 1 more Smart Citation
“…18 There is no significant link between expenditure and official payment probability in the private sector, where most people make official payments (83%), although the point estimate is 0.01 (panel B, columns 4-6). This is consistent with the observation of Amone et al (2005) that patients exempted at Catholic hospitals are typically not poor.…”
Section: Probability Of Bribingsupporting
confidence: 90%
“…The results therefore fail to support the hypothesis that competition reduces bribery. Although NGO and mission hospitals also make provision for fee exemptions for the poor, Amone et al (2005) observe that in their sample of Catholic hospitals, only a minority of exempted patients were poor (the others were predominantly hospital and church staff, and teachers and pupils of the Catholic school). Most of these hospitals charged on a fee-for-service basis (each service had an associated fee), with the exception of treatment for tuberculosis and sexually transmitted diseases including HIV/AIDS, which was funded by the government.…”
mentioning
confidence: 94%
“…Other studies conducted elsewhere have also indicated that cost is often a barrier to seeking health services especially among the poor 48,49 . Due to abolition of user fees at public health facilities, rural communities use them frequently 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Other factors are facility-based such as poor quality provision of health care services. Poor quality of health care services, specifically in East African countries, pose great challenges to health care seekers [17][18][19] .…”
Section: Short Communicationsmentioning
confidence: 99%